Urgensi Akta Kematian Dalam Proses Pewarisan Di Kota Bukittinggi Sumatera Barat - Rahma Yulia; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2026)
Inheritance is the transfer of assets from a deceased person to their heirs, and their use to improve the welfare of surviving family members and improve their lives. This means that all rights and responsibilities of the deceased are fully transferred to the heirs or other individuals entitled to the transfer. This document is a crucial type of population administration document, as without it, other population administration processes can be hampered. Presidential Regulation Number 25 of 2008 concerning Requirements and Procedures for Registering Residents and Civil Registration, in Article 1 paragraph (10) explains that